PENGARUH KONSERVATISME AKUNTANSI TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Bentar Wibisono; Fuad Fuad (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to analyze the effect of accounting conservatism to the practice of earnings management. The data used for this study is secondary data taken from the website of Indonesia Stock Exchange (IDX), specifically manufacturing companies registered in 2014-2017. Sampling for this research uses purposive sampling method, then carried out data analysis including descriptive statistics and classical assumption test. Variables used in this research are accounting conservatism as independent variable, earnings management as dependent variable, and size & ROA as control variables.Based on the result of this research, it is known that conservatism accounting and company size have significant negative effect on earnings management. Whilst ROA doesn’t have significant effect on earnings management.